The Influence of Personal Factor, Husband’s support, Health Workers and Peers toward the Use of IVA Screening among Women of Reproductive Age in the Regency of Karanganyar - Martini Shoim Wakhidah; Uki Retno Budi Hastuti; Yulia Lanti Retno Dewi (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: Cervix cancer has been one of the highest cancer cases and becomes one of the main problems in women’s health throughout the world. The percentage of Women of Reproductive Age who performs early cancer detection is an indicator of success for health development. The Regency of Karanganyar is one of the regencies in the Province of Central Java with the percentage of Women of Reproductive Age who perform Visual Inspection with Acetic Acid (IVA) is equal to 5.50%. This percentage is still far below the target that has been set which is 10.00%.Subjects and Methods: This was an analytic observational study with cross-sectional design. This study was carried out in Regency of Karanganyar. The subjects who had been involved were 150 respondents and these subjects were selected by means of fixed disease sampling. This sampling resulted in 50 cases and 100 controls. The dependent variable was behavior of using IVA screening, while the independent variables were perceived susceptibility, perceived seriousness, perceived benefits, perceived obstacles, husband’s support, health workers support, peer support, perceived threats and self-efficacy. In processing the data, the researchers implemented path analysis by means of Stata 13.Results: The results of the study showed perceived threats (b= 0.08; 95% CI= <0.01 until 0.16; p= 0.043), perceived benefits (b= 0.05; 95% CI= <-0.01 until 0.117; p= 0.091), perceived obstacles (b= -0.49; 95% CI= -0.07 until 0.11; p= 0.091), self-efficacy (b= 0.04; 95% CI= -0.13 until 0.11; p= 0.125), perceived susceptibility (b= 0.23; 95% CI= 0.11-0.34; p <0.001), perceived seriousness (b= 0.11; CI9 95%= 0.00 until 0.22; p= 0.049), husband’s support (b= 0.14; 95% CI= -0.01 until 0.29; p=0.068), health workers support (b= -0.23; 95% CI=-0.54 until 0.08; p= 0.149) and peer support (b= 0.18; 95% CI= -0.13 until 0.51; p= 0.256).Conclusion: There is a direct influence from perceived benefits, perceived obstacles, perceived threats and self-efficacy toward behavior of using IVA screening. Then, there is indirect influence from perceived susceptibility, perceived seriousness, husband’s support, health workers support and peer support toward behavior of using IVA screening.Keywords: IVA, HBM, support, path analysisCorrespondence: Martini Shoim Wakhidah. Masters Program of Public Health, Sebelas Maret University, Surakarta. Email:afkarshoim_msw@yahoo.com. Mobile: +6285235464812.Journal of Health Promotion and Behavior (2017), 2(2): 124-137https://doi.org/10.26911/thejhpb.2017.02.02.03